BIMBINGAN DAN KONSELING SEBAGAI UPAYA PENGEMBANGAN KARAKTER SISWA SEKOLAH DASAR - Mustafa (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2019)
This study aims to analyze the role of guidance and counseling in the character development of elementary school students based on a literature review. A qualitative approach was employed, specifically utilizing a library research method. The data sources consisted of seven scholarly articles published between 2015 and 2019 that were relevant to the topics of guidance and counseling and elementary student character development. The analysis involved identifying, examining, comparing, and synthesizing findings from previous research. The results indicate that guidance and counseling play a crucial role in helping students recognize their potential, boost self-confidence, develop communication skills, build social relationships, and adapt to both the school environment and the community. Classroom teachers also play a strategic role in delivering guidance and counseling services, particularly in schools that lack dedicated guidance and counseling teachers. The effectiveness of these services is influenced by teacher competence, effective communication, school support, and collaboration with parents. Thus, guidance and counseling constitute an integral part of elementary education and must be implemented systematically, sustainably, and in alignment with students' developmental needs.